As políticas educacionais para inserção de tecnologias digitais no ensino fundamental em Aracaju : uma análise do processo discursivo dos contextos de influências - Pereira, Max Augusto Franco (2022)
This research aimed to understand the discursive processes of contextualization and recontextualization of the National Curricular Common Base and the Connected Education Innovation Policy, aiming at the insertion of digital information and communication technologies and the appropriation of digital culture in elementary education in the Municipal Public Network. of Education of Aracaju (RPMEA). The theoretical script took as a reference the approach of the Educational Policy Cycle, to analyze the intercontext discursive processes of transfer policies, revealed by the categories of the theoretical approach that were represented by the macrocontexts of the transnational networks of influence and text production of educational policies, and by the local microcontext, represented by the Municipal Department of Education (SEMED) and the Municipal School of Elementary Education Oviedo Teixeira, in Aracaju. The course included a bibliographic review of liberalism, its doctrinal origin in the 17th century, in England, and a historical clipping of its political developments, in the legal system and, above all, in capitalist production and in classical economics, to understand the expression neoliberal imaginary and its mechanisms of influence, action and power, under which the Educational Policy Cycle and its contextual macro and micro categories and respective discourses of truth and power are analyzed in the post-structuralist perspective. The investigation data were collected and analyzed by the methods of network ethnography and research and documental analysis of policies, resolutions, guidelines, norms, ordinances, protocols, notebooks, and other documents, as well as semi-structured interviews with education professionals from the local microcontext. The analysis of the categories in relation to the research object revealed the presence of an emerging education ecosystem in the national market, exercised by family philanthropy organizations in partnership with corporate business organizations, startups and educational entrepreneurship, operating in public and private basic education; that the National Curricular Common Base is an integrating norm of policies of the National Education System, inspired by the theory of lifelong learning and structured in a matrix of competences and skills to be developed by students through a hybrid education for educational innovation , supported by the Connected Education Innovation Policy that links public investment funds and monitoring of resources and results. In the local microcontext, the standardization of the common base was concluded with the Pedagogical Notebooks of the Municipal Network and with the Sergipe Curriculum, schools were equipped with infrastructure, internet access technology and digital devices for teachers, but they did not advance in the implementation of the hybrid pedagogy and in the objective evaluation of the results of connected innovation policies. The analysis of the intercontext discursive process of educational policies led to the following thesis defended here: the insertion of Digital Information and Communication Technologies and the appropriation of digital culture in a structured and instrumental way as established by the BNCC will require a disruptive change in the planning process and in the implementation of pedagogical policy at SEMED and RPMEA. The change process should prioritize an inversion of the meaning of the demands for the construction of the school and the pedagogical model adapted to hybrid education, with compatible valorization, commitment, and the active participation of the actors in the RPMEA. The thesis projects that the non-occurrence of the proposed disruptive transformation will maintain the hegemony of conventional pedagogy in the school practices of the RPMEA, will hinder innovation for a connected education network, accentuate the differences in the quality of education between private and public networks and between these and it will make unfeasible equity in basic education established by law.